Radiofrequency Electromagnetic Fields from Mobile Devices used for Learning and Working - Koppel, T.; Ahonen, M. (Elektronika ir Elektrotechnika, 2013)
The relevance of this article can be described by two developments intrinsic to the digital age: the wide-spread use of the mobile devices with wireless connectivity and the exponential increase of radiofrequency electromagnetic fields in past years. The aim of this article is to determine the field strengths of popular mobile devices and to analyse their compliance in light of both legal safety limits and third-party precautionary limits. The importance of minimizing the exposure to the electromagnetic fields where possible is stressed by recent scientific evidence and also by the high level European bodies. The measurements are conducted using a novel 14-point measurement model, covering the entire body of the user. The measurement results show that the strongest fields are produced by a tablet PC, a smartphone and a netbook when they are connected to the network via EDGE or GPRS technologies. Significantly less exposure is obtained from the devices that utilize WLAN network connection or 3G within excellent network reception. At the same time, the least strong radiofrequency electromagnetic field is produced when using the e-reader or desktop PC. Based on the results, solutions are suggested to minimize the users’ field exposure while retaining the network connectivity. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.4565